Website-Based Futsal Field Reservation Information System At The Cisaat Disen Gor - Tya Septiani Nurfauzia Koeswara; Siti Khotimatul Wildah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to develop a web-based futsal court reservation information system for GOR Disen Cisaat to address inefficiencies in the existing manual booking process, such as data loss, double bookings, and delays in generating reports. The aim was to improve customer satisfaction, streamline data management, and enhance operational efficiency for the facility’s administrators. Materials and methods involved requirements analysis, system design (including UI, database schema, and navigation structure), implementation using PHP Laravel framework with MVC architecture, and MySQL as the database. The development process included building modules for user registration, booking management, payment tracking, and administrative reporting. The system was tested through functional testing scenarios to validate features and ensure reliability before deployment. Results showed that the implemented system successfully enabled customers to make online reservations anytime and anywhere, while administrators could manage court availability, bookings, and payments more efficiently. The system eliminated double bookings, accelerated report generation, and provided a structured, centralized database for reservation data. Conclusions indicate that the web-based reservation system significantly improves the management process at GOR Disen Cisaat, offering convenience for both users and administrators. Future enhancements are recommended, including stronger data security measures, mobile responsiveness, integration with online payment gateways, automated notifications, and periodic system evaluations to maintain service quality.